The Effect Of Entrepreneurship Knowledge Towards The Success Of Coffeeshop Business In Padang - Prabaningtyas, Dewi; Yelfi, Reno; Gusnita, Wiwik; Insan, Ranggi Rahimul (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research was backgrounded by the rapid development of the coffee shop business  in the city of Padang. However, problems arise in line with the level of entrepreneurial knowledge that is still inadequate so that the coffee shop business in the city of Padang does not achieve business success. The purpose of this study is 1) To describe  the entrepreneurial knowledge possessed by coffee shop business actors in the city of Padang, 2) Describe the success of the coffee shop business in the city of Padang, 3) Analyze the influence of entrepreneurial knowledge on the success  of a coffee shop business in the city of Padang. This type of research uses the quantitati f method, a causal associative approach. The population in this study was all business actors in 12 coffee shops in the city of Padang. The study sample was 36 people consisting of business owners and a management team determined by total sampling. Data is collected by distributing questionnaires. The data description uses a normal curve. The analysis requirements test was carried out with normality test, homogeneity test, linearity test and then hypothesis test was carried out using correlation test, simple regression test, and determination coefficient test with the help of SPSS Version 25.00. The results of the study, the entrepreneurial knowledge variable (X) is included in the category of quite good with a percentage of 88.9%, and the business success variable (Y) is included in the category of quite good with a percentage of 52.8%. The variable of entrepreneurial knowledge has a correlation to the success of the coffee shop business  in the city of Padang of 0.711, where the two variables have a strong relationship and are of positive value. The regression coefficient was obtained by 0.906 and the coefficient of determination was obtained by (0.506) 50.6%.